2013 IEEE International Conference on Mechatronics and Automation 2013
DOI: 10.1109/icma.2013.6618099
|View full text |Cite
|
Sign up to set email alerts
|

Deployment analysis of a planar deployable support truss structure

Abstract: As the development of space structures is increasing fast, the kinematic characteristic, dynamic characteristics, driving modes and the influence of the component parameters of a planar deployable support truss structure for space antenna are discussed by means of the closed loop equations and the Kane equation. Also several examples of kinematic and dynamic analysis results under different driving modes are presented. The results show the importance of the choice of driving movements and the design of paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Figure 8 presents a multi-closed-loop deployable mechanism which is assembled in series by two identical two-loop deployable mechanisms (TLDM) described in Figure 4. 14 This assembly mechanism is composed of 12 rods, 4 closed loops, and capable of 4 DOFs. We call it 2-TLDM in this article.…”
Section: Adjustment Of Two-loop Deployable Mechanism In Multi-configurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 8 presents a multi-closed-loop deployable mechanism which is assembled in series by two identical two-loop deployable mechanisms (TLDM) described in Figure 4. 14 This assembly mechanism is composed of 12 rods, 4 closed loops, and capable of 4 DOFs. We call it 2-TLDM in this article.…”
Section: Adjustment Of Two-loop Deployable Mechanism In Multi-configurationsmentioning
confidence: 99%
“…Patel and Ananthasuresh 13 developed a kinematic theory for radially foldable closed-loop linkages using the algebraic locus of the coupler curve. Liu and colleagues 14 discussed the deployment planar deployable support truss structure by means of the closed-loop equations and the Kane equation.…”
Section: Introductionmentioning
confidence: 99%
“…In equations (13) and (14), the first-and the second-order derivative of Ál e with respect to x, which can be derived from equation 3 Under the small displacement assumption, the second term of equation 14can be ignored. Prior to approaching equation 12, we have to form the gradient vector and the second-derivative matrix by equations (15) and (16). In this situation, Ál e can be regarded as the differences between the nominal length and the unassembled length.…”
Section: Analysis Model Involving Manufacturing Errormentioning
confidence: 99%
“…For solving the kinematics problems, the method of kinematic differentials is often used as an efficient tool. 14,15 Anantharaman and Hiller presented a simple approach to the numerical simulation of these systems. 16 Based on the Jacobian matrices, the different kinds of the singularities encountered in closed-loop chains were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Meng et al [10], Bo et al [11] and Siriguleng et al [12] proposed structure design methods of basic units and their constructed regular polygonal prisms to describe the mechanism principles of motor-driven hoop truss antennas. Liu et al [13], Wang et al [14], Guo et al [15,16], Takamatsu et al [17] and Tian et al [18,19] used experimental and numerical methods to design the truss structures, sliding hinges and driving springs of the truss antennas, aiming to ensure their reliable deployment driven by the elastic potential energy. Meanwhile, Li et al [20] and Santoni et al [21] studied the vibration characteristics of spring-deployed solar arrays on a satellite during deployment in orbit and found that the vibration of solar arrays has a larger amplitude and longer decay time under in-orbit vacuum conditions than on the ground.…”
Section: Introductionmentioning
confidence: 99%